Extrinsic and Intrinsic Factors related to Recovery Process in People with Schizophrenia - Fernandez, Aaron; Tan, Kit-Aun.; Ruziana, Masiran; Riana, Abdul Rahim (International Journal of Psychosocial Rehabilitation, 2018)
The objective of this study was to examine the associations between recovery processes, recovery-oriented practices, and symptom severity in people with schizophrenia attending clinics at Hospital Kuala Lumpur. Psychiatric diagnosis was established using the Mini international neuro-psychiatric interview. Participants completed the RSA, measures of extrinsic enablers of recovery and the RAS, measures of internal recovery characteristics. Clinicians provided ratings using the PANSS, measures of symptom severity, and the M.I.N.I., measures of psychiatric diagnosis. Recovery orientation in individuals with schizophrenia was found to be positively correlated with the presence of recovery-oriented practices in the mental health system and negatively correlated with their symptoms. Recovery-oriented practices in the mental health system as rated by participants was negatively correlated with their symptom severity. The findings of this study suggest that a recovery-oriented mental health system or milieu is positively associated with the presence of internal recovery values in people with schizophrenia and negatively related to symptom severity.